THE EFFECT OF CAPITALISM IN SUZZANE COLIN’S NOVEL THE HUNGER GAMES - Egawai Egawati; Safitri Hariani (Universitas Islam Sumatera Utara, 2022)
This research is conducted to analyze the effects of capitalism in society through the novel The Hunger Games written by Suzanne Collins and to determine the negative effects that occur in society. According to Karl Marx capitalism is the production of value and surplus-value. It is an ideology that believes that the owner of production can do their effort to get the big profit. The negative effects that are analyzed in this study are: poverty, social stratification, and totalitarianism. Poverty as deficiency materials and services needed to achieve a decent life. Poverty is a condition where a person is unable to meet basic needs such as shelter, food clothing, decent health, and education. Social stratification is system of differentiation of individuals or groups in society, which placing it in social classes that differ hierarchically and provide different rights and obligations between individuals in one layer with another layer. Totalitarianism is meant to a government that is strong, powerful, lasting and all-encompassing and within the state; nothing outside the state; nothing against the state. This research uses descriptive qualitative method. It is applied to explain the negative impact of capitalism from quotations in the novel. This research finds that the three effects of capitalism: poverty, social stratification, and totalitarianism are found the novel.